PROGRAM BIMBINGAN BELAJAR UNTUK MEMBANTU MENINGKATKAN KEMANDIRIAN BELAJAR SISWA - Heru Sriyono (Universitas Indraprasta PGRI, 2016)
This present research aims at designing the tutoring program that could develop student's independent learning at SMP Desa Putera Jakarta, as well as could create a better circumstance of learning at school. This research is carried out at SMP Desa Putera Jakarta. Findings have shown that student's independent learning profile of SMP Desa Putera Jakarta in the year of 2010/2011, the attitude of student's independent learning reached at 57.65%, the readiness and the needs of student's learning reached at 45.97%, the eagerness and future goal reached at 54.88%, student's ability and independent learning reached at 58.18%, an enjoyable learning activity reached at 57.18%. Proposed recommendation is that the school should create a pleased learning environment for the students as their independent of learning could also be well formed. Key words: Tutoring program, Independent learning